A systematic review and meta-analysis of shugan jieyu capsule combined with escitalopram in the treatment of senile depression - Xing Tang; Chengcheng Wang; Qinwan Huang; Chunxia Yang; Shoujen Lan; Yeayin Yen; Congcong Yu (Scientific Reports)
Abstract To evaluate the synergistic effect of the Shugan Jieyu Capsule combined with Escitalopram in the treatment of senile depression. The study protocol has been registered in PROSPERO with registration number CRD42023440270. Eight databases, including PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Network (CNKI), China Biomedical Literature Database (CBM), VIP database, and Wanfang Database, were searched, respectively. Randomized controlled trial (RCTs) of the Shugan Jieyu Capsule combined with Escitalopram in the treatment of senile depression was included. The search time was from the listing of Shugan Jieyu Capsule (2009) to January 1, 2025. Outcome measures included Total effective rate, Hamilton Depression Scale (HAMD) score, Hamilton Anxiety Scale (HAMA) score, serum 5-hydroxytryptamine (5-HT), serum norepinephrine (NE), and Incidence of adverse reactions. The treatment period should be at least 6 weeks. Data extraction and methodological quality evaluation were carried out for the included literature, and statistical analysis was performed using RevMan 5.3 software. Finally, the Grading of Recommendations Assessment, Development and Evaluation (GRADE ) system was used to assess the quality of the evidence. A total of 8 RCTs were included in the study, with a total of 765 patients. The results of this meta-analysis showed that the combination of Shugan Jieyu Capsule and Escitalopram could improve Total effective rate [OR = 4.25, 95%CI(2.53, 7.14), P<0.00001] and reduce HAMD score in terms of clinical symptom indicators [SMD=-1.26, 95%CI(-1.45, -1.08), P<0.00001], and decrease HAMA score [SMD=-0.82, 95%CI(-1.05, -0.59), P<0.00001]. In terms of laboratory indexes, serum 5-HT levels could be increased in the combined group [MD = 31.92, 95%CI(28.34, 35.50), P < 0.00001]. In terms of safety, no serious adverse reactions were observed in both group, and the incidence of adverse reactions was lower in the combined group [OR = 0.62, 95%CI(0.42, 0.92), P = 0.02]. During the treatment period of 12 weeks, Shugan Jieyu Capsule combined with Escitalopram had a good effect in the treatment of senile depression, which could significantly reduce HAMD and HAMA scores of senile depression. In addition, the combined application of the two drugs can help to increase the level of serum 5-HT, without increasing the occurrence of adverse events, and has a good application prospect.